Materialność świetlnego zapisu – o rzeczach w dorobku Jerzego Lewczyńskiego - Kobylińska-Bunsch, Weronika (Artium Quaestiones, 2019)
The popularity of Jerzy Lewczyński (1924-2014) coincided with the academic interest in the problem of archive, corresponding to Lewczyński’s program of the “archeology of photography,” developed in the 1970s. Lewczyński’s idea consisted in restoring Kantor’s “reality of the lowest rank,” i.e. the rejected microhistories hidden in the anonymous and the forgotten or taken out of an ashtray at the Warsaw Central train station. Today, however, one tends to forget that Lewczyński’s gesture of artistic legitimization did not aim at giving new meanings, but above all at blurring the boundary between everyday items and those which emerged from some kind of “aesthetic situation” (Maria Gołaszewska). This aspect of his art can be seen, e. g, in his visual journal, where the artist included objects of particular importance – next to Xerox copies of his own works or works of other artists, he placed also shopping receipts. Lewczyński equaled the value of cheap receipt paper with the noble velvety quality of bromine. He did not reduce his collected items to their aesthetic function, having rejected the institutionalized idea of the artifact as a work of art to enjoy by the audience. Anticipating the postulates of Bruno Latour, instead of showing objects appropriated by the power of the gaze, he presented actors: things that asked questions on their own.